Ethics: A Guide for Science - Antonius Alex Lesomar (Language, Culture, Politics)
Ethics is crucial for science. This article aims to outline the relationship between ethics and science. Science as a profession cannot be separated from ethics. Scientists require not only rigorous methods and procedures in their work but also ethics to guide them. They are demanded as experts in their fields and as good persons. Ordinary people (non-scientific society) trust reliable scientists who have good competence, skill and personality. Hence, integration of science and ethics brings up epistemic trust, on the one hand among scientists and on the other hand among scientists and non-scientific society. There are various kinds of ethics that can be a guide for the scientific work of scientists. However, in this article I offer Karol Wojtyła's personalist ethics based on the philosophy of being as a guide for science.